2016
DOI: 10.1504/ijlt.2016.079035
|View full text |Cite
|
Sign up to set email alerts
|

Student engagement in massive open online courses

Abstract: Completion rates in Massive Open Online Courses (MOOCs) are disturbingly low. Existing analysis has focused on patterns of resource access and prediction of drop-out using learning analytics. In contrast, the effectiveness of teaching programs in traditional Higher Education (HE) settings internationally is increasingly assessed by surveys measuring student engagement. The conceptualisation of engagement used is much richer and more informative than the way the term is currently interpreted in the context of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…Caulfield, Collier, and Halawa (2013) report limited participation in forums, and Milligan and Littlejohn (2014) found little exchange of ideas and experience in a MOOC on clinical trials. Sinclair and Kalvala (2016) suggest that online communities are claimed as a positive aspect of MOOCs, but that collaborative learning is underutilised. Since our findings suggest active engagement, this appears to be an aspect worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Caulfield, Collier, and Halawa (2013) report limited participation in forums, and Milligan and Littlejohn (2014) found little exchange of ideas and experience in a MOOC on clinical trials. Sinclair and Kalvala (2016) suggest that online communities are claimed as a positive aspect of MOOCs, but that collaborative learning is underutilised. Since our findings suggest active engagement, this appears to be an aspect worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In many respects, these instruments have become the proxy for our concepts of engagement, as exemplified by the widely deployed North American National Survey of Student Engagement (NSSE) developed by Indiana University. Sinclair and Kalvala (2016) suggested that the NSSE focuses on behavioural level dimensions of student engagement, and although they are cautious about the interpretation of results from this and other surveys, they also cited the work by Pascarella, Seifert, and Blaich (2010) which suggested that engagement surveys can indicate learning gain. The UK Engagement Survey (UKES) used in this study draws on a 3 (page number not for citation purpose) subset of NSSE questions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is the vector representing the complete set of M units in the hidden layer h. {(L o )} U o=1 is the vector representing the U neurons in the output layer o. In the case of a single hidden layer, the collection of weights can be represented by two matrices {W 1 ij , W 2 kj } The weight matrix which connects the input to the hidden layer can be represented as W 1 ij , and the weight matrix that links the hidden to the output layer is W 2 kj . B i L i=1 is the column vector of biases for layer i.…”
Section: ) Neural Networkmentioning
confidence: 99%
“…MOOCs provide a variety of multimedia tools to deliver an interactive learning environment. MOOCs offer valuable digital learning resources, allowing students to access information from all over the world [2].…”
Section: Introductionmentioning
confidence: 99%